Hubungan Kebahagiaan dengan Prestasi Akademik pada Mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi - Harrison, Ray; Opod, Hendri; Sinolungan, Jehosua S. V. (Universitas Sam Ratulangi, 2025)
Abstract: Academic success and achievement are important goals for students in higher education. Feeling happy in individual life can help students to achieve their academic goals. This study aimed to determine the relationship between happiness and academic achievement in students at the Faculty of Medicine, Universitas Sam Ratulangi. This was a quantitative and analytical study. Respondents were students of class 2020 at Faculty of Medicine, Universitas Sam Ratulangi. Data were obtained by using the Oxford Happiness Questionnaire (OHQ) and grade point average (GPA). The Pearson correlation test showed that from 145 students, a significant positive relationship (p=0.033) with a weak correlation (r=0.178) was found between happiness and academic achievement. In conclusioin, there is a positive relationship between happiness and academic achievement in students at the Faculty of Medicine, Universitas Sam Ratulangi. Keywords: happiness; academic achievement; medical students Abstrak: Keberhasilan dan prestasi akademik merupakan tujuan penting bagi mahasiswa dalam jenjang pendidikan yang lebih tinggi. Perasaan bahagia dan puas akan kehidupan individu dapat membantu mahasiswa mencapai tujuan akademiknya. Penelitian ini bertujuan untuk mengetahui hubungan antara kebahagiaan dengan prestasi akademik pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi dengan angkatan 2020 sebagai responden penelitian. Jenis penelitian ialah analitik kuantitatif. Data diperoleh menggunakan Oxford Happiness Questionnaire (OHQ) dan indeks prestasi kumulatif (IPK). Hasil uji korelasi Pearson menunjukkan bahwa dari 145 mahasiswa, didapatkan hubungan positif yang bermakna (p=0,033), dengan kekuatan lemah (r = 0,178), antara kebahagiaan dengan prestasi akademik. Simpulan penelitian ini ialah terdapat hubungan positif antara kebahagiaan dengan prestasi akademik pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi angkatan 2020. Kata kunci: kebahagiaan; prestasi akademik; mahasiswa kedokteran